Uptake of COVID-19 Vaccines among Pregnant Women: A Systematic Review and Meta-Analysis - Petros Galanis; Irene Vraka; Olga Siskou; Olympia Konstantakopoulou; Aglaia Katsiroumpa; Daphne Kaitelidou (Vaccines, 2022)
Mass vaccination against COVID-19 is essential to control the pandemic. COVID-19 vaccines are now recommended during pregnancy to prevent adverse outcomes. With this review, we aimed to evaluate the evidence in the literature regarding the uptake of COVID-19 vaccinations among pregnant women. A comprehensive search was performed in PubMed, Medline, Scopus, ProQuest, Web of Science, CINAHL, and medRxiv from inception to 23 March 2022. We performed a meta-analysis to estimate the overall proportion of pregnant women vaccinated against COVID-19. We found 11 studies including 703,004 pregnant women. The overall proportion of pregnant women vaccinated against COVID-19 was 27.5% (95% CI: 18.8–37.0%). Predictors of COVID-19 vaccination uptake were older age, ethnicity, race, trust in COVID-19 vaccines, and fear of COVID-19 during pregnancy. Mistrust in the government, diagnosis of COVID-19 during pregnancy, and fears about the safety and side effects of COVID-19 vaccines were reasons for declining vaccination. The global COVID-19 vaccination prevalence in pregnant women is low. A large gap exists in the literature on the factors influencing the decision of pregnant women to be vaccinated against COVID-19. Targeted information campaigns are essential to increase vaccine literacy among pregnant women.